2009
DOI: 10.1021/jp9045808
|View full text |Cite
|
Sign up to set email alerts
|

3D Bi2WO6/TiO2 Hierarchical Heterostructure: Controllable Synthesis and Enhanced Visible Photocatalytic Degradation Performances

Abstract: A three-dimensional (3D) multicomponent oxide, Bi2WO6/TiO2 as an example, hierarchical heterostructure was successfully synthesized as a mat via a simple and practical electrospinning-assisted route. The as-prepared hierarchical nanofibrous mat consisted of Bi2WO6 nanoplates growing aslant on the primary TiO2 nanofibers. Interestingly, the nanoplates were further composed of nanoparticles with a size of less than 20 nm. Bi2WO6 with different morphologies and microstructures could be obtained by adjusting the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
144
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(154 citation statements)
references
References 38 publications
5
144
0
1
Order By: Relevance
“…The mutual transfer of photogenerated charge carriers of nanomaterials of different semiconductors can enhance the photocatalytic efficiency [142][143][144]. On the basis of electron transfer process for two or more desirable semiconductors where photogenerated electrons can flow from one semiconductor with a higher CBM to the other with a lower CBM, is of great importance in better realization of photocatalytic degradation of organic pollutants [145][146][147]. It has many advantages like the oxidation and reduction processes taking place at different sites.…”
Section: Photocatalysis By Zno Nanocompositementioning
confidence: 99%
“…The mutual transfer of photogenerated charge carriers of nanomaterials of different semiconductors can enhance the photocatalytic efficiency [142][143][144]. On the basis of electron transfer process for two or more desirable semiconductors where photogenerated electrons can flow from one semiconductor with a higher CBM to the other with a lower CBM, is of great importance in better realization of photocatalytic degradation of organic pollutants [145][146][147]. It has many advantages like the oxidation and reduction processes taking place at different sites.…”
Section: Photocatalysis By Zno Nanocompositementioning
confidence: 99%
“…This is based on the fact that the photogenerated electrons can flow from one semiconductor with a higher to a lower conduction band minimum. Under such conditions, the separation of electron-hole pairs was promoted while keeping reduction and oxidation reactions at two different sites (Peng, Xie, Lu, Fan, & Wang, 2010;Shang et al, 2009;Wang et al, 2009). As a result, the efficiency of semiconductors improved (Jing, Xu, Sun, Jing, & Cai, 2001;Lin, Wu, Zhang, & Pan, 2009;Liu, Ye, Xiong, & Liu, 2010;Vaezi, 2008;Zheng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the synthesis and application of 3D hierarchical heterostructures will be a focus of the nanomaterial research field [16][17][18][19] . Mai et al have synthesized ultra-long hierarchical vanadium oxide nanowires by electrospinning, which exhibit much higher capacity in lithium ion batteries 20 .…”
mentioning
confidence: 99%
“…Meng et al synthesized 3D Bi 2 WO 6 /TiO 2 to enhance photocatalytic activity and found that the heterostructures exhibited much higher photodegradation efficiency than Bi 2 WO 6 and TiO 2 (ref. 19).…”
mentioning
confidence: 99%